Laparoscopic management of pelvi-ureteric junction obstruction caused by aberrant renal vessels in an adult - Sangoi, Chintan; Shetty, Prakashchandra; Joshi, Abhijit (Indian Journal of Case Reports, 2022)
Pelvi-ureteric junction obstruction is not a rare clinical entity. It is indeed one of the common urological conditions presenting most commonly as hydronephrosis and pain. The most common etiology for patients suffering from acquired pelvi-ureteric junction obstruction is the presence of calculus/calculi. An aberrant renal vessel (now termed as Vascular bar) is one of the causes in adults which is often missed on pre-operative investigations and is detected intra-operatively. We present herein, a case report of a 28 years old female who came with complaints of loin pain since 2 to 3 months. The workup investigations revealed only hydronephrosis without any calculi. Thus a diagnosis of primary pelvi-ureteric junction obstruction was made. The patient was successfully managed by a laparoscopic pyeloplasty.                Keywords : PUJ obstruction, Vascular bar, aberrant renal vessel, laparoscopic pyeloplasty